Study of the factors influencing the implementation and deployment of an occupational health and safety management system within Moroccan companies - Mannane, Khadija; Benhadou, Mariam; Haddout, Abdellah; Kacemi, Khadija (Edelweiss Applied Science and Technology, 2025)
Faced with the critical situation of occupational health and safety (OHS) in the industrial sector, Moroccan companies are increasingly aware of the need to adopt proactive and preventive risk management strategies. The implementation of an OHS management system appears to be a relevant response to this challenge, helping to foster a culture of safety within the workplace. This study aims to explore the motivations behind the adoption of OHS management systems, identify the main obstacles to their implementation, and propose potential solutions to facilitate their integration. The research is based on a questionnaire distributed to a representative sample of 200 Moroccan companies of varying sizes (large, medium, and small), with a response rate of 75%. The analysis of the data revealed that accident prevention and regulatory compliance are the key drivers for adopting an OHS management system. However, several barriers to implementation were also identified, including difficulties in applying legal and regulatory requirements and challenges related to the development of the necessary documentation. To address these issues, we propose a structured methodological approach aimed at supporting the straightforward and effective deployment of OHS management systems, particularly within small and medium-sized enterprises (SMEs) in Morocco.